Who counts as employed? Informal work, employment status, and labor market slack - Anat Bracha; Mary A. Burke (Federal Reserve Bank of Boston, 2016)
Several recent studies find that as of 2015, a significant share of working-age adults in the United States participates in nonstandard work arrangements. Such arrangements tend to lack long-term employment contracts and are often referred to as "gig economy" jobs. This paper investigates the implications of nonstandard or "informal" work for the measurement of employment status and labor market slack. Using original survey data, we find that as of 2015 roughly 37 percent of nonretired U.S. adults participated in some type of informal work, and roughly 20 percent participated in informal incomegenerating activities that did not exclusively involve renting out their own property or selling their own goods. The survey also elicits an individual's employment status according to the definitions of the Bureau of Labor Statistics (BLS). While not the majority, a significant share of those who engage in informal work are classified as not being in the labor force; if all informal workers were counted as employed, the U.S. labor force participation rate (as of 2015) would have been 2 percentage points higher. In addition, individuals who are classified as working "part-time for economic reasons" - those who would like a full-time job but cannot obtain full-time hours - have the highest participation rate in informal work and the highest average hours per month. This latter finding suggests that informal work embodies labor market slack, and we offer several pieces of evidence that support the thesis that workers engage in informal work as a way to compensate for weak labor demand and may therefore drop informal work as formal labor market conditions improve. To estimate the amount of labor market slack embodied in informal work, we convert the total hours of informal work performed by those classified as employed part-time into a number of full-time job equivalents. This exercise yields a figure that ranges from roughly 275,000 to roughly 400,000, depending on the specifics of the calculation. At the same time, we point out that a significant share of informal work hours offer higher wages than what the same individuals earn in their formal jobs. Therefore, formal wages may need to increase by a relatively large margin moving forward in order to attract additional labor into the formal sector.
Keywords: J21; J22; J46; E26; 330; informal work; gig economy; BLS employment status; labor market slack